Rare Association of Gullain-Barré Syndrome with Non-Hodgkins Lymphoma: A Case Report - Kundu, NC; Joy, KMNI; Sen, M; Quraishi, FA (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Guillain-Barré Syndrome (GBS) is a very common cause of acute motor neuropathy in medical ward, though its association with lymphoma is not very common. Here we present a case of acute motor neuropathy which was clinically diagnosed as a case of GBS. CSF (Cerebrospinal fluid) study and electrophysiological study supported the clinical diagnosis. The patient also had generalized lymphadenopathy & histopathological examination of lymph node revealed high grade Non-Hodgkins Lymphoma (NHL). A staging bone marrow study was performed which revealed lymphoreticular malignancy. The case was finally diagnosed as GBS with stage IV Non-Hodgkins Lymphoma. DOI: http://dx.doi.org/10.3329/jbcps.v31i3.20986 J Bangladesh Coll Phys Surg 2013; 31: 168-173